Processors, pipelines, and protocols for advanced modeling networks - Coughlan, J.C.; Bjorkstead, E.P. (2001 IEEE International Geoscience and Remote Sensing, 2001)
NASA's Earth Science Enterprise has established the goal of developing a predictive capability for the Earth System. NASA uses the vantage point of space to provide information about Earth's land, atmosphere, ice, oceans, and biota that is obtainable in no other way. To enhance predictive capabilities, NASA is planning a sensor web to collect data across a range of spatio-temporal scales. The end-to-end process of data collection, data assimilation, biogeophysical modeling and prediction is inseparable and predominately enabled by software. Software transforms the raw data into usable products and information and software disseminates these products to end-users. New information system technologies are needed to enable better prediction, flexible data assimilation and model coupling to build integrated Earth system models. Advancement of our modeling capabilities will require not only faster processing, but new programming methods, new algorithms, high-speed data pipelines, and interoperable architectures that allow the networking of diverse Earth System models.